The Effect of Competency Training and Development on Employee Work Effectiveness at the XYZ District Office - Junengsih Junengsih; Fa'uzobihi Fa'uzobihi; Intan Oktavia; Pradnya Sari Harsanti (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Human resources are a very important part of the organization in achieving its goals and objectives. The purpose of this research is to find out whether competency training and development affect the work effectiveness of employees at the XYZ sub-district office. This study used a quantitative approach, by applying observation and questionnaires to 36 XYZ sub-district office employees, using SPSS 22 statistical software. The results showed that both partially and simultaneously the Training and Competency Development variables had a positive and significant effect on Employee Work Effectiveness in XYZ district office.